Inhalable microspheres embedding chitosan-coated PLGA nanoparticles for 2-methoxyestradiol. (June 2014) - Guo, XinHong; Zhang, XinXin; Ye, Ling; Zhang, Ying; Ding, Rui; Hao, YongWei; Zhao, YaLin; Zhang, ZhenZhong; Zhang, Yun
Abstract Developing a highly effective and lung-targeted local drug delivery carrier with low irritancy may be critical for improving treatment of lung cancer. Using soluble excipients as microspheres (MS) matrix, respirable MS embedding chitosan-coated poly(d, l-lactide-co-glycolide) nanoparticles (CNP-MS) for 2-methoxyestradiol (2-ME) were designed, which could avoid macrophage phagocytosis to achieve the targeted delivery of these drugs. 2-ME CNP-MS were prepared by spray-drying and characterized by morphology, redispersability, fine particle fraction (FPF) and drug release. Cytotoxicity, and lung deposition and histological examination were investigated. Results showed that 2-ME CNP-MS were spherical with a rough surfaces, exhibiting good redispersability, a high respirable fraction and sustained release characteristics. CNP-MS markedly enhanced the cytotoxicity of 2-ME by approximately 8.8-fold and 3.65-fold on SPC-A1 cells compared to solution and NP, respectively. After pulmonary administration, 2-ME CNP were distributed in rat lungs and for 10 mg of 2-ME CNP-MS, haematoxylin and eosin staining showed no obvious difference compared to the untreated control group. Therefore, CNP-MS revealed suitable features for local lung delivery and significantly enhanced cytotoxicity of 2-ME without obvious inflammation in lungs of rats, suggesting that 2-ME CNP-MS have great potential as an inhalation agent for targeted, highly effective and safe treatment of lung cancer.